2023
DOI: 10.3389/fimmu.2023.1170475
|View full text |Cite
|
Sign up to set email alerts
|

ARID5B regulates fatty acid metabolism and proliferation at the Pre-B cell stage during B cell development

Abstract: During B cell development in bone marrow, large precursor B cells (large Pre-B cells) proliferate rapidly, exit the cell cycle, and differentiate into non-proliferative (quiescent) small Pre-B cells. Dysregulation of this process may result in the failure to produce functional B cells and pose a risk of leukemic transformation. Here, we report that AT rich interacting domain 5B (ARID5B), a B cell acute lymphoblastic leukemia (B-ALL) risk gene, regulates B cell development at the Pre-B stage. In both mice and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that the risk allele lowers ARID5B expression 7 and that dysregulation of this gene affects B-cell hematopoiesis. 12,13 Why this results in increased risk specifically for HeH ALL is not known. A characteristic feature of the HeH subtype is the nonrandom gain of chromosomes, with an extra copy of chromosome 10, that carries ARID5B, being seen in 70% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that the risk allele lowers ARID5B expression 7 and that dysregulation of this gene affects B-cell hematopoiesis. 12,13 Why this results in increased risk specifically for HeH ALL is not known. A characteristic feature of the HeH subtype is the nonrandom gain of chromosomes, with an extra copy of chromosome 10, that carries ARID5B, being seen in 70% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Constitutional single nucleotide polymorphisms (SNPs) in the ARID5B gene at 10q21.2, which codes for a member of the AT‐rich interactive domain (ARID) protein family involved in chromatin‐remodeling, 1,2 are associated with an increased risk of developing childhood B cell precursor acute lymphoblastic leukemia (BCP ALL), particularly of the high hyperdiploid (HeH; 51–67 chromosomes) subtype 3–11 as well as with an increased risk of relapse of pediatric ALL 6,7,9 . Two recent publications have reported that ARID5B expression plays an important role in regulating hematopoiesis at the pre‐B‐stage 12,13 . In a mouse model, Chalise et al 12 showed that deletion of ARID5B led to a significant reduction in immature B cells.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations